2017
DOI: 10.1007/s10535-016-0699-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma modified growth and physiology in Triticum aestivum via generated signaling molecules and UV radiation

Abstract: The current research was carried out to reveal the possible impacts of cold plasma on growth and physiology of wheat, as a new approach in plant science. Short and long-term impacts of different types of plasma (nitrogen and helium) with surface power density of 0.4 W cm-2 , exposure times (15, 30, 60, and 120 s), and repetitions (1, 2, and 4 times with 24 h intervals) were evaluated. Single-time applied helium or nitrogen derived plasma significantly promoted total root and shoot lengths, in contrast to four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…In this study, both positive and inhibitory responses associated with the plasma priming in C. roseus are presented. In line with our findings, numerous reports are exhibiting the growth‐stimulating function of plasma priming in diverse plant species, while little evidence exists on growth‐inhibitory or delaying response following plasma application . Taking the plasma diagnostic data into account, we recently reported that the optical emission spectroscopy‐based spectrum confirmed the generation of oxygen‐ and nitrogen‐related species, as well as UV photons during the plasma generation .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, both positive and inhibitory responses associated with the plasma priming in C. roseus are presented. In line with our findings, numerous reports are exhibiting the growth‐stimulating function of plasma priming in diverse plant species, while little evidence exists on growth‐inhibitory or delaying response following plasma application . Taking the plasma diagnostic data into account, we recently reported that the optical emission spectroscopy‐based spectrum confirmed the generation of oxygen‐ and nitrogen‐related species, as well as UV photons during the plasma generation .…”
Section: Discussionsupporting
confidence: 90%
“…In radish, the application of plasma‐activated water and seed treatment led to a significant improvement in seed germination, and the plant's early growth was attributed to the plasma‐modified chemical composition, especially nitric oxide and hydrogen peroxide in water . In good agreement with our results, it has been stated that plasma time should be optimized depending on plant species …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There is little or no information for establishing crop stress management practices using plasma technology. To our knowledge, there are only a few studies under laboratory conditions on crop tolerance to disease (Jiang et al, 2014b;Ochi et al, 2017), drought (Li et al, 2015;Guo et al, 2017;Feng et al, 2018), salinity (Iranbakhsh et al, 2018), and oxidative stress (Bußler et al, 2015;Iranbakhsh et al, 2017) using plasma technology. Therefore, further studies are needed to optimize the effectiveness of plasma treatment on crop tolerance to a broad range of stressors.…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%
“…The response of seeds to plasma treatment was shown to depend on plasma gas composition: apparent (wheat) seed growth inhibition symptoms occurred in samples exposed to nitrogen plasma than in samples exposed to helium plasma, attributed to the higher NO content [14].…”
Section: Quality Retentionmentioning
confidence: 99%